Dampak Kecanduan Game Online Terhadap Kesehatan Mental Remaja Dan Penanganannya Dalam Konseling Islam - Niswah, Zulfatun; Naqiya, Chulayla; Dewi, Salsha Putri Riana; Kibtyah, Maryatul (BKI IAIN Pontianak, 2023)
Abstract: The use of online games can be categorized as one of the advances that are in great demand by various age categories, especially among adolescents. Continuous use of online games can cause users to experience addiction and affect health. Among adolescents who have been categorized as experiencing online game addiction, of course, the most common health problems encountered are higher emotional distress, anxiety, depression, and social behavior. Addiction to online games will have different impacts on its users. This study aims to examine online game addiction disorder and its treatment in Islamic counseling. The research method used in this study is a descriptive qualitative approach with a case study research design. The results of this study prove that the problem of online game addiction disorder among adolescents and its impact on mental health can be handled by taking an Islamic counseling approach.